239Pu fallout across continental Australia: Implications on 239Pu use as a soil tracer. (November 2017) - Lal, R.; Fifield, L.K.; Tims, S.G.; Wasson, R.J.
Abstract: At present there is a need for the development of new radioisotopes for soil erosion and sediment tracing especially as fallout 137 Cs levels become depleted. Recent studies have shown that 239 Pu can be a useful new soil erosion and sediment radioisotope tracer. 239 Pu was released in the major atmospheric nuclear weapons tests of 1950's and 1960's. However 239 Pu has a half-life of 24110 years and more than 99% of this isotope is still present in the environment today. In contrast 137 Cs with a half-life of 30.07 year has decayed to <35% of initially deposited activities and this isotope will become increasingly difficult to measure in the coming decades especially in the southern hemisphere, which received only about a third of the total global fallout from the atmospheric tests (UNSCEAR, 2000). In this study an assessment of the 239 Pu fallout in Australia was carried out from comparison of measured 239 Pu inventories with expected 239 Pu inventories from fallout models. 239 Pu inventories were also compared with rainfall and measured 240 Pu/ 239 Pu ratios across Australia. 239 Pu fallout inventories ranged from 430 to 1461 μB/cm 2 . Central Australia, with fallout 107% in excess of expected values, seems to be strongly impacted by local fallout deposition. In comparison other sites typically show 5–40% variation between expected and measured fallout values. The fallout inventories were found to weakly correlate (using power functions, y = a x b ) with rainfall with r 2 = 0.50 across the southern catchments (25–40°S latitude band). Across the northern catchments (10–25°S latitude band) fallout showed greater variability with rainfall with r 2 = 0.24. Central Australia and Alice Springs which seem to be strongly impacted by local fallout are excluded from the rainfall correlation data (with these sites included r 2 = 0.08 and r 2 < 0.01 respectively). 240 Pu/ 239 Pu atom ratios range from 0.045 to 0.197, with averages of 0.139(0.017), 0.111(0.052) and 0.160(0.027) in the 10–20°S, 20–30°S and 30–40°S latitude bands respectively. The 240 Pu/ 239 Pu atom ratios in Central Australia (0.069) likely represent fallout from the Australian tests which also have low 240 Pu/ 239 Pu atom ratios i.e., Maralinga (0.113) and Montebello (0.045). The average ratios in the 20–30°S and 30–40° bands are closer to the global average (0.139 and 0.177 respectively when not including the close-in fallout data from the nuclear test sites) if the Australian test sites and Central Australian sites are neglected as they clearly represent the effects of close in fallout.